Readings in public administration -I - Bhattacharya, P. (ed.) (Kolkata, 2005)
The first ATI monograph was, in keeping with its motto, "LEARNING TO SERVE", appropriately The Right Attitude to Work and the Right Spirit. This was followed by monographs on the financial and service rules of the state government.
Keywords: Public administration